Neotheory of Continuous Mediums Thermomechanics (Global Journal of Science Frontier Research, 2019)
Abstract not found
Keywords: medium; continuous; solid; fluid; thermomechanics; models; traditional; antinomies; limitations; alternative; systems of counting